Impact of Front Line Demonstration on Yield and Profitablitiy of Chickpea (Cicer arietinum Linn) in Banswara district of Rajasthan - Bhati, Bheroo Singh; Ramawtar; Soni , R. L.; Bugalia, H. L. (Indian Journal of Extension Education, 2018)
Chickpea (Cicer arietinum Linn) is the major pulse crop used in the diet of vegetarian in India and it is a good source of  protein. Front line demonstration were conducted at 119 farmers field under 47.6 ha in 16 villages, to demonstrate  production potential and economic benefits of improved technologies consisting suitable varieties (PC-1) with seed rate  of 75 kg / ha, line sowing with spacing of 30 cm (R-R) and 20 cm (P-P), seed treatment, balanced dose of fertilizer, weed  management and plant protection measures. The demonstrations were carried out at Banswara district of Rajasthan during  rabi 2013-14 to 2015-16. The improved technologies recorded mean yield of 12.37 q/ha which was 53.42 per cent higher  than that obtained with farmers practice of 8.05 q/ha. Improved technologies gave higher mean net return of `18016 / ha  with a benefit cost ratio of 1.79 as compared to local practice (` 5932 / ha, benefit cost ratio 1.29)
Keywords: Chickpea; demonstration; FLD programme; productivity